Ritualised discourse practices of feedback in a university foundation programme: a critical investigation - Richardson, Amy (Rhodes University, Faculty of Humanities, Department of Linguistics and Applied Language Studies, 2012)
In order for students to become true members of academic communities of practice they need epistemological access, including guidance on central institutional knowledge-producing processes and mastery of key academic literacy practices. A powerful source of guidance is marker feedback. Drawing on key insights from the New Literacy Studies and taking up the mandate of Critical Ethnography to improve the status quo, this thesis reports on the feedback practices in a university foundation programme. The findings are based on three micro-case studies compiled and analysed by means of methods drawn from Ethnography, Sociolinguistics and Critical Analysis in conjunction with an expanded, multimodal, APPRAISAL analysis, including adjusted categories and the author's own feedback typologies. Two major arguments emerge: the feedback provided amounts to a set of ritualised discourse practices and its effects can be likened to the product of the children's game of Head-body-tail. Consequently, feedback conventions are opaque and, potentially, impede epistemological access. They further entrench five sets of ideologies: (1) Students must master basic English literacy before they are coached in more complex issues such as argumentation; an assumption which leads to differential socialisation. (2) There is a single set of literacy practices that is rewarded. (3) Students have different levels of authorial authority depending on their language abilities. (4) 'Middle students' may benefit the most from feedback. (5) Specific comments are preferred over general ones. Analysis of feedback, furthermore, shows that markers' frames of reference shape their pedagogy and that draft and final versions of work may be framed differently by markers. These findings require a response and, in order to facilitate epistemological access, suggestions are made for improved marker training based on the problematisation of the ritual involved in marking students' work in this university foundation programme.
Keywords: Uncatalogued